The Spirituality of Urban Society - Guslita Siadeka; Taslim M. Yasin; Sehat Ihsan Shadiqin (Winaya Inspirasi Nusantara Foundation, 2020)
The phenomenon of roving morning prayers in the city of Banda Aceh is a new thing in Acehnese society. Supposedly, as an area that implements Islamic law with a majority Muslim community, the congregational dawn movement is not a strange thing. Because the morning congregation is an integral part of the implementation of Islamic teachings, this appears as a new movement in urban society. The main problems in this research are: how this movement initially appeared in the city of Banda Aceh. Then also see how the motivation of worshipers who follow What is the impact on society? This research uses descriptive qualitative methods in obtaining data using several techniques, namely observation, interviews, and documents, to analyze the data using descriptive qualitative methods. Acehnese society is known as a religious society that always upholds fundamental religious values. but now it has slowly begun to be eroded by the swift flow of globalization. Because the results of the globalization process, in fact, are able to anesthetize the human soul to always be addicted to technology as a vehicle for modern life, making humans forget what they have. Such a condition exists in Acehnese society for the people of the origin of life to seek the meaning of religion in life. This group plays a role in accommodating the spiritual needs of the community. One of the places to be able to express closeness to God is with the emergence of the Fajr prayer movement in congregations in Banda Aceh City. The presence of the congregational morning prayer movement in the public sphere has provided a new color in terms of Islamic spiritual experience, as seen from the number of congregants who follow and also receive support from the community and government as well. In terms of spirituality, there are two sides obtained from the congregational morning prayer movement, namely, the vertical spiritual side. The congregational morning prayer movement establishes a relationship with the creator through worship in the form of congregational prayer. Then, from the horizontal side, this movement can become a place for friendship between fellow Muslims in the city of Banda Aceh.